Adhesive tape for electronic component processing and method for manufacturing electronic component
Patent Information
- Application Number
- JP2023133652
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2025-03-03
AI Technical Summary
【0013】 本開示は、酸素により硬化阻害を抑制することが可能な電子部品加工用粘着テープを提供できる。
Smart Images

Figure 2025028692000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an adhesive tape for processing electronic components and a method for manufacturing electronic components. [Background technology]
[0002] In a so-called dicing process in which a substrate to be processed is divided into chips, an adhesive tape called a dicing tape is used to protect and fix the substrate to be processed and the chips.
[0003] As such adhesive tapes, for example, photocurable adhesive tapes have been actively developed.
[0004] Recently, a dicing method using a laser guided by a water jet has been proposed, which will be hereinafter referred to as water jet laser processing.
[0005] An adhesive tape usually has a substrate and an adhesive layer. For example, as described in Patent Documents 1 to 4, in the case of water jet laser processing, a mesh sheet or the like that is permeable to water flow is used as the substrate constituting the adhesive tape in order to suppress chipping caused by splashing water. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 3824874 [Patent Document 2] Patent No. 4087144 [Patent Document 3] Patent No. 5000370 [Patent Document 4] JP 2005-167042 A Summary of the Invention [Problem to be solved by the invention]
[0007] In photocurable adhesive tapes, the adhesive layer is cured by irradiation with light, thereby reducing the adhesive strength. When a mesh sheet is used, oxygen in the air comes into contact with the adhesive layer through the openings of the mesh sheet, which causes the adhesive layer to be inhibited from curing by oxygen. If the adhesive layer is not cured sufficiently, the adhesive strength of the adhesive layer does not decrease sufficiently, and cracks or chips occur in the chip when the adhesive tape is peeled off.
[0008] As a method for suppressing the inhibition of curing caused by oxygen in the air, for example, a nitrogen purging method is known, but this requires special equipment and increases costs.
[0009] Patent Document 2 also proposes a technique for preventing the curable adhesive layer from coming into contact with oxygen and suppressing curing inhibition caused by oxygen in the air by disposing a non-curable adhesive layer between a substrate and a curable adhesive layer in an adhesive tape used in water jet laser processing. However, when the adhesive tape further has a non-curable adhesive layer, the manufacturing process is increased, resulting in higher costs.
[0010] The present disclosure has been made in consideration of the above-mentioned situation, and has as its main object to provide an adhesive tape for processing electronic components, which has a photocurable adhesive layer disposed in contact with a mesh sheet, and which is capable of suppressing curing inhibition caused by oxygen. [Means for solving the problem]
[0011] One embodiment of the present disclosure is an adhesive tape for processing electronic components, comprising a mesh sheet and a photocurable adhesive layer disposed on one side of the mesh sheet in contact with the mesh sheet, wherein the adhesive tape for processing electronic components has an oxygen inhibition influence rate represented by the following formula (1) of 30% or less. Oxygen inhibition effect rate (%) = [(adhesive strength to glass plate after light irradiation in air / adhesive strength to glass plate after light irradiation in nitrogen atmosphere)-1] × 100 (1)
[0012] Another embodiment of the present disclosure provides a method for manufacturing electronic components, comprising: an attachment step of attaching the above-mentioned adhesive tape for electronic component processing to a first surface of a workpiece substrate; a dicing step of dividing the workpiece substrate into a plurality of chips; an irradiation step of irradiating light to the adhesive layer of the adhesive tape for electronic component processing to harden it; and a peeling step of peeling the adhesive tape for electronic component processing from the chip. Effect of the Invention
[0013] The present disclosure can provide an adhesive tape for processing electronic components that can suppress curing inhibition due to oxygen. [Brief description of the drawings]
[0014] [Figure 1] 1 is a schematic cross-sectional view illustrating an example of an adhesive tape for processing electronic components according to the present disclosure. [Diagram 2] 1 is a schematic cross-sectional view illustrating an example of an adhesive tape for processing electronic components according to the present disclosure. [Diagram 3] 1A and 1B are schematic plan and cross-sectional views illustrating a mesh sheet constituting an adhesive tape for processing electronic components according to the present disclosure. [Figure 4] 1A to 1C are process diagrams illustrating a method for manufacturing an electronic component according to the present disclosure. [Diagram 5] 1A to 1C are process diagrams illustrating a method for manufacturing an electronic component according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The following describes the embodiments of the present disclosure with reference to the drawings. However, the present disclosure can be implemented in many different forms and should not be limited to the description of the embodiments exemplified below. In addition, the drawings may be schematic in terms of the width, thickness, shape, etc. of each part compared to the actual form in order to make the explanation clearer, but these are merely examples and should not be interpreted as being limited. In this specification and each figure, the same reference numerals are used to designate elements similar to those described above with respect to the previous figures, and detailed descriptions may be omitted as appropriate.
[0016] In this specification, when describing an aspect in which another component is disposed on a certain component, the term "above" or "below" includes both cases in which another component is disposed directly above or below a certain component so as to be in contact with the component, and cases in which another component is disposed above or below a certain component with another component interposed therebetween, unless otherwise specified. In addition, in this specification, when describing an aspect in which another component is disposed on the surface of a certain component, the term "on the surface" includes both cases in which another component is disposed directly above or below a certain component so as to be in contact with the component, and cases in which another component is disposed above or below a certain component with another component interposed therebetween, unless otherwise specified.
[0017] In this specification, the term "sheet" also includes a member called a "film."
[0018] The adhesive tape for processing electronic components and the method for producing electronic components according to the present disclosure will be described below.
[0019] A. Adhesive tape for electronic parts processing The adhesive tape for electronic component processing according to the present disclosure comprises a mesh sheet and a photocurable adhesive layer disposed on one side of the mesh sheet in contact with the mesh sheet, and has an oxygen inhibition influence rate represented by the following formula (1) of 30% or less. Oxygen inhibition effect rate (%) = [(adhesive strength to glass plate after light irradiation in air / adhesive strength to glass plate after light irradiation in nitrogen atmosphere)-1] × 100 (1)
[0020] Fig. 1 is a schematic cross-sectional view illustrating an example of an adhesive tape for electronic component processing according to the present disclosure. As illustrated in Fig. 1, an adhesive tape for electronic component processing 10 has a mesh sheet 1 and a photocurable adhesive layer 2 disposed on one side of the mesh sheet 1 in contact with the mesh sheet 1.
[0021] In the present disclosure, the above formula (1) was derived in order to suppress the curing inhibition caused by oxygen. The oxygen inhibition influence rate represented by the above formula (1) is an index for comparing the curing of the adhesive layer under the atmosphere with the curing of the adhesive layer under a nitrogen atmosphere. If the adhesive layer is cured under the atmosphere in the same way as under a nitrogen atmosphere, the value of "adhesive strength to a glass plate after light irradiation under the atmosphere / adhesive strength to a glass plate after light irradiation under a nitrogen atmosphere" will be close to 1. Therefore, the oxygen inhibition influence rate will be low. On the other hand, if the adhesive layer is not cured sufficiently under the atmosphere, the value of "adhesive strength to a glass plate after light irradiation under the atmosphere / adhesive strength to a glass plate after light irradiation under a nitrogen atmosphere" will be greater than 1 and farther from 1. Therefore, the oxygen inhibition influence rate will be high. Therefore, the lower the oxygen inhibition influence rate, the more effective it is in suppressing the curing inhibition caused by oxygen.
[0022] Therefore, in the present disclosure, by setting the oxygen inhibition influence rate represented by the above formula (1) to a predetermined value or less, it is possible to suppress the inhibition of curing by oxygen. As a result, the adhesive layer can be easily peeled off after light irradiation, so that cracking or chipping of the chip when peeling off the adhesive tape for processing electronic components can be suppressed. In addition, since there is no need to perform nitrogen purging during light irradiation and light irradiation can be performed under atmospheric air, it is possible to reduce costs and improve workability.
[0023] Hereinafter, each component of the adhesive tape for processing electronic components according to the present disclosure will be described.
[0024] 1. Characteristics of adhesive tapes for electronic component processing (1) Oxygen inhibition effect rate In the adhesive tape for processing electronic components according to the present disclosure, the oxygen inhibition influence ratio represented by the following formula (1) is 30% or less, may be 20% or less, or may be 10% or less. By having the oxygen inhibition influence ratio be equal to or less than a predetermined value, it is possible to suppress curing inhibition caused by oxygen. On the other hand, as described above, the lower the oxygen inhibition influence ratio, the more effective it is in suppressing curing inhibition caused by oxygen, so the lower limit of the oxygen inhibition influence ratio is not particularly limited. The value of the oxygen inhibition influence ratio may be negative.
[0025] Oxygen inhibition effect rate (%) = [(adhesive strength to glass plate after light irradiation in air / adhesive strength to glass plate after light irradiation in nitrogen atmosphere)-1] × 100 (1)
[0026] The adhesive strength to a glass plate after light irradiation in the atmosphere is measured by the following method. First, in accordance with method 1 of the test method of JIS Z0237:2022 (Test method for adhesive tapes and adhesive sheets) (temperature 23°C, humidity 50%, test method in which the tape and sheet are peeled off at 180° from a stainless steel test plate), a test piece 25 mm wide is taken from the adhesive tape for electronic component processing, and the test piece is attached to a glass plate. The glass plate is float glass (size 150 mm x 70 mm, thickness 2 mm) manufactured by Osaka Glass Industry Co., Ltd. Next, the laminate with the glass plate and the test piece is placed in a nitrogen purge box for light irradiation. Next, using an H bulb of an electrodeless lamp bulb manufactured by Heraeus, the exposure amount of 500 mJ / cm at a wavelength of 365 nm is measured. 2 Next, in accordance with JIS Z0237:2022 (Test methods for adhesive tapes and adhesive sheets), Method 1 (a test method in which the tape or sheet is peeled off at 180° to a stainless steel test plate at a temperature of 23°C and humidity of 50%), the adhesive strength to the glass plate is measured by peeling off the test piece in the length direction at a separation angle of 180° and a peeling speed of 300 mm / min.
[0027] The adhesive strength to a glass plate after light irradiation in a nitrogen atmosphere is measured by the following method. First, in accordance with JIS Z0237:2022 (Test method for adhesive tapes and adhesive sheets) Test Method 1 (temperature 23°C, humidity 50%, tape and sheet are peeled off at 180° from a stainless steel test plate), a test piece with a width of 25 mm is taken from the adhesive tape for electronic component processing, and the test piece is attached to a glass plate. The glass plate is the same as the glass plate described above. Next, the laminate having the glass plate and the test piece is placed in a nitrogen purge box for light irradiation. After that, the nitrogen purge box is filled with nitrogen, and the valve is closed and sealed. At this time, nitrogen is filled so that the oxygen concentration is 10000±5000 ppm. Next, using an H bulb of an electrodeless lamp bulb manufactured by Heraeus, the exposure amount of a wavelength of 365 nm is 500 mJ / cm.2 Next, in accordance with JIS Z0237:2022 (Test methods for adhesive tapes and adhesive sheets), Method 1 (a test method in which the tape or sheet is peeled off at 180° to a stainless steel test plate at a temperature of 23°C and humidity of 50%), the adhesive strength to the glass plate is measured by peeling off the test piece in the length direction at a separation angle of 180° and a peeling speed of 300 mm / min.
[0028] The Heraeus H-bulb electrodeless lamp reproduces the spectrum of a high-pressure mercury lamp and efficiently emits 254 nm, 313 nm, and 365 nm. High-pressure mercury lamps or light sources that reproduce the spectrum of a high-pressure mercury lamp are often used in light irradiation devices. Therefore, Heraeus H-bulb electrodeless lamps were used to measure the adhesive strength to the glass plate after light irradiation.
[0029] Methods for controlling the oxygen inhibition effect rate include, for example, a method for adjusting the light transmittance of the mesh sheet, a method for adjusting the light transmittance of the adhesive layer, a method for adjusting the content of the polymerization initiator in the adhesive layer, a method for adjusting the type of the polymerization initiator, a method for adjusting the number of functional groups in the photocurable compound, a method for adjusting the content of the photocurable compound in the adhesive layer, and a method for adjusting the type of the photocurable compound.
[0030] The high light transmittance of the mesh sheet and the adhesive layer allows the light to reach deep into the adhesive layer when the adhesive tape for electronic component processing is irradiated with light from the mesh sheet side, enhancing the internal curing property, thereby reducing the adhesive strength to the glass plate after light irradiation in the atmosphere and reducing the oxygen inhibition effect rate.
[0031] By increasing the content of the polymerization initiator in the adhesive layer, the amount of active species generated from the polymerization initiator increases, so that the curing property can be improved, and therefore the adhesive strength to the glass plate after light irradiation in the atmosphere can be reduced, and the oxygen inhibition influence rate can be reduced.
[0032] By using a polymerization initiator that generates active species with high reactivity, the curing property can be improved. Therefore, the adhesive strength to a glass plate after light irradiation in the atmosphere can be reduced, and the oxygen inhibition influence rate can be reduced. Specifically, an oxime ester-based polymerization initiator that generates active species with high reactivity can be mentioned.
[0033] (2) Adhesion to glass plates In the adhesive tape for processing electronic parts, the adhesive strength to a glass plate before light irradiation may be, for example, 0.5 N / 25 mm or more and 40 N / 25 mm or less.
[0034] The adhesive strength to the glass plate before light irradiation is measured according to JIS Z0237:2022 (Adhesive tape and adhesive sheet test method) method 1 (temperature 23°C, humidity 50%, tape and sheet peeled at 180° to stainless steel test plate), by peeling the test piece in the length direction under the conditions of width 25mm, peel angle 180°, and peel speed 300mm / min. The glass plate is the same as the glass plate described above.
[0035] In addition, the adhesive strength of the adhesive tape for electronic component processing to a glass plate after light irradiation in the atmosphere is preferably, for example, 2.0 N / 25 mm or less. The lower limit of the adhesive strength to a glass plate after light irradiation in the atmosphere is not particularly limited, and is, for example, 0.01 N / 25 mm or more.
[0036] The method for measuring the adhesive strength to the glass plate after light irradiation in the atmosphere is as described above.
[0037] 2. Adhesive layer The adhesive layer in the present disclosure is a photocurable member disposed on the first surface of the mesh sheet. The photocurable adhesive layer is cured by irradiation with light, and its adhesive strength is reduced. In the dicing process, the photocurable adhesive layer can fix the substrate to be processed or the divided chips due to its initial adhesive strength. In addition, in the peeling process, the photocurable adhesive layer can be peeled off from the chips because its adhesive strength is reduced and peelability is improved by curing the layer by irradiation with light.
[0038] Examples of light include ultraviolet light and visible light, with ultraviolet light being preferred.
[0039] (1) Adhesive layer material The adhesive layer is not particularly limited as long as it satisfies the above-mentioned characteristics, and may contain, for example, a resin (adhesive base), a photocurable compound, and a polymerization initiator. When the adhesive layer contains a photocurable compound, the photocurable compound can be cured by irradiation with light, thereby reducing the adhesive strength. In addition, the cohesive strength increases at this time, making it easier to peel off.
[0040] (a) Resin (main adhesive) Examples of the resin (adhesive base) include resins that are generally used as adhesive bases, such as acrylic resins, polyester resins, polyimide resins, and silicone resins. Among these, acrylic resins are preferred. By using acrylic resins, adhesive residue on the adherend can be reduced.
[0041] Therefore, the adhesive layer preferably contains an acrylic resin, a photocurable compound, a polymerization initiator, and a crosslinking agent. In the adhesive layer, the acrylic resin is usually present as a crosslinked body formed by crosslinking between acrylic resins with the crosslinking agent, but a simple acrylic resin may be contained together with the crosslinked body.
[0042] (Acrylic resin) The acrylic resin is not particularly limited, and examples thereof include (meth)acrylic acid ester polymers obtained by homopolymerizing (meth)acrylic acid esters, and (meth)acrylic acid ester copolymers obtained by copolymerizing (meth)acrylic acid esters with other monomers, with (meth)acrylic acid esters as the main component. Among these, (meth)acrylic acid ester copolymers are preferred. Specific examples of (meth)acrylic acid esters and other monomers include those disclosed in JP 2012-31316 A. The other monomers can be used alone or in combination of two or more kinds. The main component here means that the copolymerization ratio is 51% by mass or more, and preferably 65% by mass or more.
[0043] Among these, as the acrylic resin, a (meth)acrylic acid ester copolymer having a (meth)acrylic acid ester as the main component and obtained by copolymerizing the (meth)acrylic acid ester with a hydroxyl group-containing monomer copolymerizable with the (meth)acrylic acid ester, or a (meth)acrylic acid ester copolymer having a (meth)acrylic acid ester as the main component and obtained by copolymerizing a hydroxyl group-containing monomer and a carboxyl group-containing monomer copolymerizable with the (meth)acrylic acid ester can be preferably used.
[0044] In this specification, (meth)acrylic acid refers to at least one of acrylic acid and methacrylic acid.
[0045] The copolymerizable hydroxyl group-containing monomer and carboxyl group-containing monomer are not particularly limited, and for example, the hydroxyl group-containing monomer and carboxyl group-containing monomer disclosed in JP-A-2012-31316 can be used.
[0046] The weight average molecular weight of the acrylic resin is, for example, preferably from 200,000 to 1,000,000, and more preferably from 200,000 to 800,000. By setting the weight average molecular weight of the acrylic resin within the above range, sufficient initial adhesive strength can be exhibited.
[0047] In this specification, the weight average molecular weight is a polystyrene-equivalent value measured by gel permeation chromatography (GPC). The weight average molecular weight is measured, for example, by using a measuring device HLC-8220GPC manufactured by Tosoh Corporation, a column TSKGEL-SUPERMULTIPORE-HZ-M manufactured by Tosoh Corporation, a solvent THF, and standard polystyrenes with molecular weights of 1050, 5970, 18100, 37900, 96400, and 706000 as standards.
[0048] In addition, when the acrylic resin is a (meth)acrylic acid ester copolymer of a hydroxyl group-containing monomer and a carboxyl group-containing monomer copolymerizable with the (meth)acrylic acid ester, the mass ratio of the hydroxyl group-containing monomer to the carboxyl group-containing monomer is, for example, preferably 51:49 to 100:0, and more preferably 75:25 to 100:0. If the mass ratio of each monomer is within the above range, an effective decrease in adhesive strength due to light irradiation can be expected, and the occurrence of adhesive residue can be suppressed.
[0049] The acrylic resin may be photocurable, for example, may have a photocurable functional group in a side chain. The photocurable functional group preferably has an ethylenically unsaturated bond, and specific examples thereof include a (meth)acryloyl group, a vinyl group, and an allyl group.
[0050] (b) Photocurable compound The photocurable compound is not particularly limited as long as it is polymerizable upon irradiation with light, and examples thereof include compounds having a photocurable functional group.
[0051] Examples of the photocurable compound include photocurable monomers, photocurable oligomers, and photocurable polymers. The photocurable polymer is a polymer different from the resin (adhesive base). Among them, photocurable oligomers are preferred from the viewpoint of the balance of adhesive strength before and after light irradiation. Also, photocurable monomers, photocurable oligomers, and photocurable polymers may be used in combination. For example, when a photocurable monomer is used in addition to a photocurable oligomer, the adhesive layer is cured by three-dimensional crosslinking when irradiated with light to reduce the adhesive strength, and the cohesive strength is increased to prevent transfer to the chip side.
[0052] Examples of photocurable compounds include radically polymerizable compounds, cationic polymerizable compounds, and anionic polymerizable compounds. Among them, radically polymerizable compounds are preferred. They have a high curing speed, can be selected from a wide variety of compounds, and can easily control physical properties such as adhesive strength before and after light irradiation.
[0053] In addition, the adhesive strength after the light irradiation can be controlled by adjusting the number of photocurable functional groups of the photocurable compound. As described above, for example, when the number of photocurable functional groups is increased, the crosslink density of the adhesive layer after the light irradiation tends to be increased, and the adhesive strength after the light irradiation tends to be decreased.
[0054] In the photocurable compound, the number of photocurable functional groups is preferably 2 or more in one molecule, more preferably 3 or more in one molecule, and even more preferably 4 or more. If the number of photocurable functional groups is within the above range, the crosslinking density of the adhesive layer after light irradiation is sufficient, so that the desired peelability can be achieved. In addition, the occurrence of adhesive residue due to a decrease in cohesive force can be suppressed. In addition, the upper limit of the number of photocurable functional groups is not particularly limited.
[0055] The photocurable compound is preferably a radical polymerizable oligomer, more preferably a radical polymerizable polyfunctional oligomer, such as those disclosed in JP2012-31316A.
[0056] In addition, as the photocurable compound, a radical polymerizable oligomer and a radical polymerizable monomer may be used, and among them, a radical polymerizable polyfunctional oligomer and a radical polymerizable polyfunctional monomer may be used. Examples of the radical polymerizable monomer include those disclosed in JP-A-2010-173091.
[0057] Examples of the photocurable compound include (meth)acrylate monomers, (meth)acrylate oligomers, (meth)acrylate polymers, etc. Examples of the photocurable compound that can be used include urethane (meth)acrylate, polyester (meth)acrylate, and epoxy (meth)acrylate.
[0058] In addition, the photocurable compound may be a commercially available product. For example, urethane acrylate "Shikou UV7620EA (molecular weight: 4100)" manufactured by Mitsubishi Chemical Corporation, urethane acrylates "Art Resin UN-905 (molecular weight: 50000 to 210000)", "Art Resin UN-905DU1 (molecular weight: 26000)", "Art Resin UN-951SC (molecular weight: 12500)", "Art Resin UN-952 (molecular weight: 6500 to 9500)", "Art Resin UN-953 (molecular weight: 14000 to 40000)", "Art Resin UN-954 (molecular weight: 4200)", and "Art Resin H-219 (molecular weight: 10000 to 15000)" manufactured by Negami Chemical Industries, Ltd. Examples of suitable polymers include "Art Resin H-315M (molecular weight: 6600)" and "Art Resin H-417M (molecular weight: 4000)" manufactured by Taisei Fine Chemical Co., Ltd., "8BR-600 (molecular weight: 100000)" acrylic urethane polymer manufactured by Taisei Fine Chemical Co., Ltd., "Unidic V-6850" polymer acrylate manufactured by DIC Corporation, "SMP-250AP (molecular weight: 20000-30000)" and "SMP-360A (molecular weight: 20000-30000)" manufactured by Kyoeisha Chemical Co., Ltd., and "HA7975" acrylic resin acrylate manufactured by Showa Denko Materials Co., Ltd.
[0059] The photocurable compounds may be used alone or in combination of two or more kinds.
[0060] The weight average molecular weight of the photocurable compound is not particularly limited, but is preferably 30,000 or less, more preferably 10,000 or less, and even more preferably 8,000 or less. If the weight average molecular weight of the photocurable compound is within the above range, it exhibits sufficient compatibility with the acrylic resin (adhesive base agent), and the adhesive layer exhibits the desired adhesive strength before light irradiation, and after light irradiation, the occurrence of adhesive residue is suppressed, making it easy to peel off. On the other hand, the weight average molecular weight of the photocurable compound is, for example, 500 or more.
[0061] In addition, the adhesive strength after light irradiation can be controlled by adjusting the content of the photocurable compound. If the content of the photocurable compound is high, the adhesive strength after light irradiation tends to be low.
[0062] The content of the photocurable compound is, for example, preferably 5 parts by mass or more and 150 parts by mass or less, more preferably 20 parts by mass or more and 100 parts by mass or less, and even more preferably 50 parts by mass or more and 80 parts by mass or less, relative to 100 parts by mass of the resin (main adhesive agent). If the content of the photocurable compound is within the above range, the crosslink density of the adhesive layer after light irradiation is sufficient, so that the desired peelability can be achieved. In addition, the occurrence of adhesive residue due to a decrease in cohesive force can be suppressed.
[0063] (c) Polymerization initiator As the polymerization initiator, a general photopolymerization initiator can be used, among which acylphosphine oxide-based, α-hydroxyalkylphenone-based, and oxime ester-based initiators are preferred.
[0064] Examples of the acylphosphine oxide polymerization initiator include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphenylphosphine oxide, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and ethyl(2,4,6-trimethylbenzoyl)-phenylphosphine oxide.
[0065] An example of the α-hydroxyalkylphenone polymerization initiator is 1-hydroxycyclohexyl-phenyl ketone.
[0066] Examples of the oxime ester polymerization initiator include 1,2-octanedione-1-[4-(phenylthio)phenyl]-2-(O-benzoyloxime) and ethanone-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(O-acetyloxime).
[0067] As described later, resins and the like can be used for the mesh sheet, and many resins absorb light with wavelengths up to about 300 nm, but transmit light with wavelengths of 300 nm or more. Acylphosphine oxide-based polymerization initiators tend to have relatively large absorption in the wavelength range of 350 nm or more. Therefore, acylphosphine oxide-based polymerization initiators can absorb light with wavelengths of 300 nm or more widely and efficiently generate active species. In addition, acylphosphine oxide-based polymerization initiators have a photobleaching effect and are excellent in internal curing. Therefore, by increasing the content of acylphosphine oxide-based polymerization initiators in the adhesive layer, the amount of active species generated can be increased and the curing property can be improved. Therefore, the adhesive strength to the glass plate after light irradiation under atmospheric conditions can be reduced, and the oxygen inhibition influence rate can be reduced.
[0068] Specifically, the content of the acylphosphine oxide polymerization initiator in the adhesive layer is preferably 7.5 parts by mass or more per 100 parts by mass of the resin (main adhesive). By having a high content of the acylphosphine oxide polymerization initiator in the above range, the oxygen inhibition influence rate can be reduced as described above. On the other hand, the content of the acylphosphine oxide polymerization initiator in the adhesive layer is, for example, 20 parts by mass or less per 100 parts by mass of the resin (main adhesive). If the content of the acylphosphine oxide polymerization initiator is too high, the cohesive force decreases, which may cause the occurrence of glue residue.
[0069] Since the polymerization initiator is expensive, it is not common to increase the content of the polymerization initiator to the above range. In addition, when the content of the polymerization initiator is increased, when the adhesive layer is irradiated with light to harden it, the transmittance of the main wavelength decreases, making it difficult for light to reach the deep part (surface part) of the adhesive layer, and the adhesive strength may not decrease easily. Specifically, when the content of the polymerization initiator is 7.5 parts by mass per 100 parts by mass of resin (main adhesive), approximately 63% of the main wavelength is absorbed. In addition, when the content of the polymerization initiator is 20 parts by mass per 100 parts by mass of resin (main adhesive), approximately 97% of the main wavelength is absorbed. This has a significant effect when a single-wavelength light source such as an LED or black light is used.
[0070] In addition, the absorption wavelength peaks are different between the acylphosphine oxide polymerization initiator and the α-hydroxyalkylphenone polymerization initiator. Therefore, by using the acylphosphine oxide polymerization initiator and the α-hydroxyalkylphenone polymerization initiator in combination, light can be absorbed widely and active species can be efficiently generated. In addition, as described above, the acylphosphine oxide polymerization initiator has a photobleaching effect and is excellent in internal curing. Therefore, by using the acylphosphine oxide polymerization initiator and the α-hydroxyalkylphenone polymerization initiator in combination, the amount of active species generated can be increased and the curing property can be improved. Therefore, the adhesive force to the glass plate after light irradiation under the atmosphere can be reduced, and the oxygen inhibition influence rate can be reduced.
[0071] When an acylphosphine oxide-based polymerization initiator and an α-hydroxyalkylphenone-based polymerization initiator are used in combination, the total content of the acylphosphine oxide-based polymerization initiator and the α-hydroxyalkylphenone-based polymerization initiator in the adhesive layer may be, for example, 0.01 parts by mass or more, or 0.5 parts by mass or more, relative to 100 parts by mass of the resin (main adhesive agent). On the other hand, the total content may be, for example, 20 parts by mass or less, or 10 parts by mass or less, relative to 100 parts by mass of the resin (main adhesive agent). That is, the total content may be, for example, 0.01 parts by mass or more and 20 parts by mass or less, or 0.5 parts by mass or more and 10 parts by mass or less, relative to 100 parts by mass of the resin (main adhesive agent). If the total content is too small, the polymerization reaction of the photocurable compound may not occur sufficiently, and the adhesive strength of the adhesive layer after light irradiation may become excessively high, making it impossible to realize peelability. On the other hand, if the total content is too large, the cohesive strength may decrease, which may cause the occurrence of glue residue.
[0072] In addition, the oxime ester polymerization initiator generates active species with high reactivity. Therefore, the curing property can be improved. In addition, the oxime ester polymerization initiator easily breaks bonds by light irradiation to generate radicals, so that the reactivity is high. Therefore, the adhesive strength to a glass plate after light irradiation in the atmosphere can be reduced, and the oxygen inhibition influence rate can be reduced.
[0073] The content of the oxime ester-based polymerization initiator in the adhesive layer may be, for example, 0.01 parts by mass or more, or 0.5 parts by mass or more, relative to 100 parts by mass of the resin (main adhesive agent). On the other hand, the content may be, for example, 10 parts by mass or less, or 2 parts by mass or less, relative to 100 parts by mass of the resin (main adhesive agent). That is, the content may be, for example, 0.01 parts by mass or more and 10 parts by mass or less, or 0.5 parts by mass or more and 2 parts by mass or less, relative to 100 parts by mass of the resin (main adhesive agent). If the content is too small, the polymerization reaction of the photocurable compound may not occur sufficiently, and the adhesive strength of the adhesive layer after light irradiation may become excessively high, making it impossible to realize peelability. On the other hand, if the content of the polymerization initiator is too large, the cohesive strength may decrease, which may cause the occurrence of glue residue.
[0074] In addition, the oxime ester polymerization initiator may be combined with another polymerization initiator. In this case, the same effect as above can be obtained. The other polymerization initiator is not particularly limited as long as it does not have absorption that inhibits polymerization by the oxime ester polymerization initiator, but an acylphosphine oxide polymerization initiator is preferable. As described above, since the acylphosphine oxide polymerization initiator has a photobleaching effect, it is considered that it is difficult to inhibit polymerization by the oxime ester polymerization initiator. In this case, the content of the oxime ester polymerization initiator in the adhesive layer is preferably within the above-mentioned range. In addition, in this case, the total content of the oxime ester polymerization initiator and the other polymerization initiator in the adhesive layer is, for example, 0.01 parts by mass or more, and may be 0.5 parts by mass or more, relative to 100 parts by mass of the resin (main adhesive agent). On the other hand, the total content is, for example, 20 parts by mass or less, and may be 10 parts by mass or less, relative to 100 parts by mass of the resin (main adhesive agent). That is, the total content may be, for example, 0.01 to 20 parts by mass, or 0.5 to 10 parts by mass, relative to 100 parts by mass of the resin (main adhesive agent). If the total content is too small, the polymerization reaction of the photocurable compound does not occur sufficiently, and the adhesive strength of the adhesive layer after light irradiation becomes excessively high, and peelability may not be achieved. On the other hand, if the total content is too large, the cohesive strength decreases, which may cause glue residue.
[0075] (d) Crosslinking Agent The adhesive layer may contain a crosslinking agent in addition to the resin (main adhesive agent) and the photocurable compound.
[0076] The crosslinking agent is not particularly limited as long as it crosslinks at least between resins (main adhesives), and is appropriately selected according to the type of resin (main adhesive). For example, isocyanate-based crosslinking agents, epoxy-based crosslinking agents, metal chelate-based crosslinking agents, etc. are included. Specific examples of isocyanate-based crosslinking agents and epoxy-based crosslinking agents include those disclosed in JP2012-31316A. The crosslinking agents can be used alone or in combination of two or more.
[0077] The content of the crosslinking agent is appropriately set according to the type of the crosslinking agent, and is preferably 0.01 to 15 parts by mass, more preferably 0.01 to 10 parts by mass, relative to 100 parts by mass of the resin (main adhesive agent). If the content of the crosslinking agent is less than the above range, the adhesion may be poor, or the adhesive layer may undergo cohesive failure when peeling off the chip, resulting in adhesive residue. On the other hand, if the content of the crosslinking agent exceeds the above range, the crosslinking agent may remain in the adhesive layer after light irradiation as an unreacted monomer, which may cause adhesive residue due to a decrease in cohesive force.
[0078] (e) Additives The adhesive layer may contain various additives as necessary, such as a tackifier, an antistatic agent, a plasticizer, a silane coupling agent, a metal chelating agent, a surfactant, an antioxidant, an ultraviolet absorbing agent, a colorant, a preservative, an antifoaming agent, and a wettability adjusting agent.
[0079] (2) Thickness of adhesive layer The thickness of the adhesive layer may be any thickness that provides a desired adhesive strength, for example, 10 μm or more, 25 μm or more, or 50 μm or more. The mesh sheet has an uneven surface due to openings and non-openings. The thickness of the adhesive layer is a predetermined value or more, so that the uneven surface of the mesh sheet can be flattened. This increases the adhesion between the adhesive sheet for electronic components and the substrate or chip to be processed, and suppresses chip flying during water jet laser processing. If the thickness of the adhesive layer is too thin, the adhesion with the mesh sheet may decrease. If the thickness of the adhesive layer is too thin, the adhesive layer may be inhibited by oxygen from the mesh sheet side of the adhesive layer, resulting in poor curing. On the other hand, the thickness of the adhesive layer is, for example, 200 μm or less. If the thickness of the adhesive layer is too thick, the water permeability may decrease.
[0080] In addition, as illustrated in Figure 2, when the mesh sheet is a mesh fabric 1A, the thickness T of the adhesive layer 2 is defined as the length from the reference plane S to the outermost surface of the adhesive layer 2 on the mesh fabric 1A side, when the outermost surface of the mesh fabric 1A on the adhesive layer 2 side is defined as the reference plane S.
[0081] (3) Method for forming adhesive layer The adhesive layer can be formed, for example, by applying an adhesive composition onto a separator. After the adhesive layer is formed, a mesh sheet is placed on the adhesive layer to obtain an adhesive tape for processing electronic components having the mesh sheet, adhesive layer, and separator in this order.
[0082] 3.Mesh sheet The mesh sheet in the present disclosure is a member that supports the adhesive layer.
[0083] The mesh sheet may be, for example, a mesh fabric or a punched sheet, which is a sheet having holes formed therein.
[0084] (1) Mesh fabric 3(a) to (c) are schematic plan views and cross-sectional views illustrating a mesh fabric in the adhesive tape for electronic component processing of the present disclosure. FIG. 3(b) is an enlarged view of FIG. 3(a), and FIG. 3(c) is a cross-sectional view of FIG. 3(b). As shown in FIG. 3(a) to (c), the mesh fabric 1A is composed of warp threads 21 and weft threads 22. In addition, the mesh fabric 1A has an opening 23 surrounded by the warp threads 21 and weft threads 22, and a non-opening 24 other than the opening 23, which has the warp threads 21 and weft threads 22, in a plan view. In FIG. 3(a) to (c), a1 indicates the wire diameter of the warp threads 21, a2 indicates the wire diameter of the weft threads 22, b1 indicates the opening between the warp threads 21, and b2 indicates the opening between the weft threads 22.
[0085] The material of the mesh fabric preferably has a high transmittance of the wavelength of the laser used in the water jet laser processing. The material of the mesh fabric may be, for example, a chemical fiber, a natural fiber, or an inorganic fiber. The chemical fiber may be, for example, a polyolefin, a polyester, a polyamide, a polycarbonate, an acrylic resin, a polyvinyl chloride, a polyurethane, a polystyrene, a styrene-ethylene-butene copolymer, a styrene-ethylene-pentene copolymer, a rayon, or a cellulose acetate. The polyolefin may be, for example, a polyethylene, a polypropylene, a polybutene, an ethylene-propylene copolymer, an ethylene-vinyl acetate copolymer (EVA), an ethylene-methyl methacrylate copolymer (EMMA), or an ionomer. The polyester may be, for example, a polyethylene terephthalate. The polyamide may be, for example, a nylon 6, a nylon 6,6, a nylon 12, or an aramid. The natural fiber may be, for example, a cotton, a silk, or a wool. The inorganic fiber may be, for example, a glass fiber or a carbon fiber. These may be used alone or in combination of two or more.
[0086] The weaving method of the mesh fabric is not particularly limited, and examples thereof include plain weave, twill weave, and satin weave.
[0087] The warp and weft threads may each be a monofilament or a multifilament, of which a monofilament is preferred because the monofilament is less likely to break during water jet laser processing.
[0088] The average diameter of the yarn is, for example, 60 μm or more, 80 μm or more, or 100 μm or more. The average diameter of the yarn is, for example, 1000 μm or less, 500 μm or less, or 300 μm or less. That is, the average diameter of the yarn is, for example, 60 μm or more and 1000 μm or less, 80 μm or more and 500 μm or less, or 100 μm or more and 300 μm or less. If the average diameter is too small, the strength of the mesh sheet may decrease and handling may become difficult. On the other hand, if the average diameter is too large, water permeability may be impaired. In addition, when the yarn is a multifilament, the average diameter of the yarn refers to the average diameter of the multifilament.
[0089] Here, the average thread diameter is the arithmetic mean value of the diameters of 10 randomly selected warp threads and 10 randomly selected weft threads. The warp thread diameter and the weft thread diameter are measured using a digital microscope. The digital microscope used can be Keyence's "Digital Microscope VHX-2000."
[0090] The opening ratio of the mesh fabric is, for example, 10% or more, may be 20% or more, or may be 30% or more. The opening ratio of the mesh fabric is, for example, 80% or less, may be 70% or less, or may be 60% or less. That is, the opening ratio of the mesh fabric is, for example, 10% or more and 80% or less, may be 20% or more and 70% or less, or may be 30% or more and 60% or less. If the opening ratio is too small, water permeability may be impaired. On the other hand, if the opening ratio is too large, adhesion to the adhesive layer may be reduced.
[0091] The opening ratio B (%) of the mesh fabric is expressed by the following formula. B=[C / (C+A)] 2 ×100 In the above formula, A is the average yarn diameter (μm) and C is the average opening between the yarns (μm).
[0092] The average opening between the threads is preferably smaller than the chip size, for example, on the order of millimeters or less. The average opening between the threads is, for example, 500 μm or less, may be 200 μm or less, or may be 100 μm or less. The average opening between the threads is, for example, 1 μm or more, may be 5 μm or more, or may be 10 μm or more. That is, the average opening between the threads is, for example, 1 μm or more and 500 μm or less, may be 5 μm or more and 200 μm or less, or may be 10 μm or more and 100 μm or less. If the average opening is too small, water permeability may be impaired. On the other hand, if the average opening is too large, adhesion to the adhesive layer may be reduced.
[0093] The average inter-yarn opening is the arithmetic mean value of the openings between 10 randomly selected warp threads and between 10 randomly selected weft threads. The openings between the warp threads and between the weft threads are measured using a digital microscope. The digital microscope used can be Keyence's "Digital Microscope VHX-2000."
[0094] When measuring the diameter of the warp yarn, the diameter of the weft yarn, the opening between the warp yarns, and the opening between the weft yarns, the adhesive layer is removed from the adhesive tape for electronic component processing, and the mesh sheet is taken out. The adhesive layer can be removed by dissolving the adhesive layer with a solvent. The solvent can be the same as that contained in the adhesive composition used to form the adhesive layer.
[0095] (2) Punching sheet The material of the punching sheet preferably has a high transmittance of the wavelength of the laser used in the water jet laser processing. Examples of the material of the punching sheet include resin. The resin is not particularly limited as long as it can be processed to make holes.
[0096] The shape of the holes in a plan view is not particularly limited, and examples of the shape include a square, a rectangle, a circle, an ellipse, a square with rounded corners, a rectangle with rounded corners, and a hexagon. The arrangement of the holes is not particularly limited.
[0097] The opening ratio of the punched sheet is, for example, 10% or more, may be 20% or more, or may be 30% or more. The opening ratio of the punched sheet is, for example, 80% or less, may be 70% or less, or may be 60% or less. That is, the opening ratio of the punched sheet is, for example, 10% or more and 80% or less, may be 20% or more and 70% or less, or may be 30% or more and 60% or less. If the opening ratio is too small, water permeability may be impaired. On the other hand, if the opening ratio is too large, adhesion to the adhesive layer may be reduced.
[0098] The opening ratio of the punched sheet is calculated appropriately depending on the planar shape of the holes, the size of the holes, the hole pitch, the arrangement of the holes, and the like.
[0099] The size of the hole is preferably smaller than the chip size, for example, on the order of millimeters or less. The size of the hole is, for example, 500 μm or less, may be 200 μm or less, or may be 100 μm or less. The size of the hole is, for example, 1 μm or more, may be 5 μm or more, or may be 10 μm or more. That is, the size of the hole is, for example, 1 μm or more and 500 μm or less, may be 5 μm or more and 200 μm or less, or may be 10 μm or more and 100 μm or less. If the size of the hole is too small, the water permeability may be impaired. On the other hand, if the size of the hole is too large, the adhesion to the adhesive layer may be reduced.
[0100] The size of the hole is the arithmetic average of 10 randomly selected holes. The size of the hole is defined according to the shape of the hole in plan view. For example, the size of the hole is the diameter for a circle, the major axis for an ellipse, the diagonal length for a square or rectangle, and the maximum diagonal length for a hexagon. The size of the hole is measured using a digital microscope. The Keyence Digital Microscope VHX-2000 can be used as the digital microscope.
[0101] When measuring the size of the hole, the adhesive layer is removed from the adhesive tape for processing electronic parts, and the mesh sheet is taken out. The method for removing the adhesive layer is as described above.
[0102] (3) Characteristics of the mesh sheet The light transmittance of the mesh sheet is not particularly limited, but may be, for example, 50% or more, 70% or more, or 90% or more. The upper limit of the light transmittance of the mesh sheet is not particularly limited. When the light transmittance of the mesh sheet is high within the above range, reflection of light by the mesh sheet can be suppressed when the adhesive tape for electronic component processing is irradiated with light from the mesh sheet side to cure the adhesive layer. This can suppress poor curing of the adhesive layer.
[0103] The optical transmittance of the mesh sheet is the transmittance of the light used when dicing the substrate to be processed using the adhesive tape for electronic component processing. For example, when ultraviolet light is used, as described above, a high-pressure mercury lamp or a light source that reproduces the spectrum of a high-pressure mercury lamp is often used in the ultraviolet irradiation device. The dominant wavelength of the high-pressure mercury lamp is 365 nm. Therefore, in this case, the optical transmittance of the mesh sheet is the transmittance of the wavelength of 365 nm.
[0104] The thickness of the mesh sheet is not particularly limited as long as it can support the adhesive layer. The thickness of the mesh sheet is, for example, 60 μm or more, may be 80 μm or more, or may be 100 μm or more. The thickness of the mesh sheet is, for example, 1000 μm or less, may be 500 μm or less, or may be 300 μm or less. That is, the thickness of the mesh sheet is, for example, 60 μm or more and 1000 μm or less, may be 80 μm or more and 500 μm or less, or may be 100 μm or more and 300 μm or less.
[0105] The thickness of the mesh sheet is measured using a thickness gauge such as a dial thickness gauge or a digital thickness gauge, and the arithmetic average value of the thicknesses at 10 randomly selected points is taken as the thickness.
[0106] When measuring the thickness of the mesh sheet, the adhesive layer is removed from the adhesive tape for processing electronic components, and the mesh sheet is taken out. The method for removing the adhesive layer is as described above.
[0107] 4. Other configurations The adhesive tape for processing electronic components according to the present disclosure may have other components, if necessary, in addition to the mesh sheet and adhesive layer described above.
[0108] The pressure-sensitive adhesive tape for processing electronic components according to the present disclosure may have a separator on the surface of the pressure-sensitive adhesive layer opposite the mesh sheet.
[0109] 5.Applications The adhesive tape for electronic component processing in the present disclosure can be used as a dicing tape. In particular, the adhesive tape for electronic component processing in the present disclosure can be suitably used as a dicing tape when dicing a workpiece substrate by laser processing. In particular, the adhesive tape for electronic component processing in the present disclosure can be suitably used as a dicing tape when dicing a workpiece substrate by water jet laser processing.
[0110] B. Manufacturing methods for electronic components The method for manufacturing electronic components in the present disclosure includes an application step of applying the above-mentioned adhesive tape for electronic component processing to one side of a workpiece substrate, a dicing step of dividing the workpiece substrate into a plurality of chips, an irradiation step of irradiating the adhesive layer of the adhesive tape for electronic component processing with light to harden it, and a peeling step of peeling the adhesive tape for electronic component processing from the chips.
[0111] 4(a) to (f) are process diagrams showing an example of a method for manufacturing electronic components according to the present disclosure. First, as shown in FIG. 4(a), a bonding process is performed in which one side of the adhesive tape 10 for electronic component processing is bonded to a ring frame 31, and a substrate 11 to be processed is bonded to one side of the adhesive tape 10 for electronic component processing. Next, as shown in FIG. 4(b), a dicing process is performed in which the substrate 11 to be processed is divided into chips 12. Next, as shown in FIG. 4(c), an expanding process is performed in which the adhesive tape 10 for electronic component processing is stretched to widen the gap between the chips 12. Next, as shown in FIG. 4(d), an irradiation process is performed in which the adhesive layer of the adhesive tape 10 for electronic component processing is irradiated with light 32 from the mesh sheet side to harden the adhesive layer, thereby reducing the adhesive strength. Next, as shown in FIG. 4(e), a pick-up process is performed in which the chip 12 is peeled off from the adhesive tape 10 for electronic component processing and the chip 12 is picked up. This pick-up process is a peeling process. Next, as shown in FIG. 4(f), a mounting (die bonding) step is performed in which the picked up chip 12 is attached to a substrate 30.
[0112] 5(a) to (e) are process diagrams showing another example of the manufacturing method of electronic components in the present disclosure. First, as shown in FIG. 5(a), an adhesive tape 10 for electronic component processing is attached to a ring frame 31, and then an attachment process is performed in which a substrate 11 to be processed is attached to the adhesive tape 10 for electronic component processing. Next, as shown in FIG. 5(b), a dicing process is performed in which the substrate 11 to be processed is divided into chips 12. Next, as shown in FIG. 5(c), a transfer tape 40 is attached to the surface of the chip 12 opposite to the adhesive tape 10 for electronic component processing, and then, as shown in FIG. 5(d), an irradiation process is performed in which the photocurable adhesive layer of the adhesive tape 10 for electronic component processing is irradiated with light from the mesh sheet side to harden the adhesive layer, thereby reducing the adhesive strength. Next, as shown in FIG. 5(e), a transfer process is performed in which the adhesive tape 10 for electronic component processing is peeled off from the chip 12 and the ring frame 31, and the chip 12 and the ring frame 31 are transferred to the transfer tape 40. This transfer process is a peeling process.
[0113] In the present disclosure, the above-mentioned adhesive tape for electronic component processing is used, so that the curing inhibition due to oxygen in the irradiation process can be suppressed. As a result, in the peeling process, the adhesive layer of the adhesive tape for electronic component processing can be easily peeled off, so that the chip cracking and chipping can be suppressed. In addition, since there is no need to perform nitrogen purging in the irradiation process and it can be performed under atmospheric air, the cost can be reduced and the workability can be improved.
[0114] A general method can be applied to each step in the method for producing an electronic component according to the present disclosure.
[0115] In particular, in the dicing step, it is preferable to divide the substrate into a plurality of chips by a laser guided by a water jet. General conditions can be adopted for the water jet laser processing.
[0116] The present disclosure is not limited to the above-described embodiments. The above-described embodiments are merely examples, and anything that has substantially the same configuration as the technical idea described in the claims of the present disclosure and exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES
[0117] The present disclosure will be further described below with reference to examples and comparative examples.
[0118] [Example 1] An adhesive composition was prepared by diluting 100 parts by mass of adhesive base agent (acrylic acid copolymer), 50 parts by mass of urethane acrylate (ultraviolet-curable compound, 9 functional groups, molecular weight 4100, active content 65%), 7.5 parts by mass of photopolymerization initiator (IGM Resins BV "Omnirad 819"), and 3 parts by mass of crosslinking agent (isocyanate-based curing agent (tolylene diisocyanate (TDI)-based adduct type (trimethylolpropane adduct)), solid content 75%) with a mixed solvent of toluene and methyl ethyl ketone (mass ratio 1:1) and thoroughly dispersing the mixture.
[0119] The above adhesive composition was applied onto a polyethylene terephthalate (PET) separator ("PET50x1-M-J2" manufactured by Nippa Corporation, thickness 50 μm) so that the thickness after drying would be 50 μm, and the composition was dried in an oven at 110°C for 3 minutes to form an adhesive layer.
[0120] A nylon mesh sheet (NBC Meshtec Corporation's "NB90") was laminated onto the adhesive layer, and then aging was carried out at 40°C for 3 days to prepare an adhesive tape for processing electronic components.
[0121] [Examples 2 to 4 and Comparative Examples 1 to 4] An adhesive tape for processing electronic components was prepared in the same manner as in Example 1, except that the type of polymerization initiator and the content of the polymerization initiator per 100 parts by mass of the adhesive base (acrylic acid copolymer) were changed as shown in Table 1 below.
[0122] [evaluation] (1) Adhesion to glass plates Using the above-mentioned measurement method, the adhesive strength of the adhesive tape for electronic component processing to a glass plate before light irradiation, the adhesive strength to a glass plate after light irradiation in the atmosphere, and the adhesive strength to a glass plate after light irradiation in a nitrogen atmosphere were measured.
[0123] (2) Oxygen inhibition effect rate The oxygen inhibition effect rate represented by the above formula (1) was calculated.
[0124] (3) Pick-up ability Adhesive tape for electronic component processing was attached to a ring frame for 6-inch wafers, and a 6-inch silicon wafer with a thickness of 100 μm was adhered and fixed to the adhesive tape for electronic component processing. Using a water jet laser processing dicing device ("Laser Microjet" manufactured by SYNOVA), the silicon wafer was divided into 10 mm square chips under conditions of a cutting speed of 100 mm / s, laser wavelength of 532 nm, water jet diameter of 40 μm, and water pressure of 250 Bar. Next, using an H bulb of an electrodeless lamp bulb manufactured by Heraeus, an exposure dose of 500 mJ / cm2 with a wavelength of 365 nm was applied to the adhesive layer of the adhesive tape for electronic component processing from the mesh sheet side. 2 The chip was then peeled off by hand. The presence or absence of cracks in the chip was then visually observed. The pickup property was evaluated according to the following criteria: A: There were no cracks. B: There was a crack.
[0125] [Table 1]
[0126] It was confirmed that the pick-up property was good and the curing inhibition due to oxygen was suppressed when the oxygen inhibition influence rate was equal to or less than a predetermined value as in Examples 1 to 4. On the other hand, in Comparative Examples 1 to 4, the pick-up property was poor because the oxygen inhibition influence rate was large. [Explanation of symbols]
[0127] 1 … Mesh sheet 2 … Adhesive layer 10...Adhesive tape for electronic component processing
Claims
1. An adhesive tape for processing electronic components, comprising: a mesh sheet; and a photocurable adhesive layer disposed on a first surface of the mesh sheet in contact with the mesh sheet, An adhesive tape for processing electronic components, having an oxygen inhibition influence rate represented by the following formula (1) of 30% or less. Oxygen inhibition effect rate (%) = [(adhesive strength to a glass plate after light irradiation in air / adhesive strength to a glass plate after light irradiation in a nitrogen atmosphere) - 1] x 100 (1)
2. The adhesive layer contains an adhesive base agent, a photocurable compound, and an acylphosphine oxide-based polymerization initiator, 2. The adhesive tape for processing electronic components according to claim 1, wherein the content of the acylphosphine oxide-based polymerization initiator in the adhesive layer is 7.5 parts by mass or more per 100 parts by mass of the main adhesive agent.
3. 2. The adhesive tape for processing electronic components according to claim 1, wherein the adhesive layer contains an adhesive base, a photocurable compound, an acylphosphine oxide-based polymerization initiator, and an α-hydroxyalkylphenone-based polymerization initiator.
4. 2. The adhesive tape for processing electronic parts according to claim 1, wherein the adhesive layer contains a main adhesive agent, a photocurable compound, and an oxime ester-based polymerization initiator.
5. a bonding step of bonding the adhesive tape for electronic component processing according to any one of claims 1 to 4 to a first surface of a substrate to be processed; a dicing step of dividing the substrate into a plurality of chips; an irradiation step of irradiating the adhesive layer of the adhesive tape for processing electronic components with light to cure it; a peeling step of peeling the adhesive tape for processing electronic components from the chip; The method for manufacturing an electronic component includes the steps of:
6. The method for producing an electronic component according to claim 5 , wherein in the dicing step, the workpiece substrate is divided into a plurality of chips by a laser guided by a water jet.
Citation Information
Patent Citations
JP1975000370A
Adhesive tape for fixing semiconductor wafer
JP2005167042A
water permeable adhesive tape
JP3824874B2
Adhesive tape for laser dicing
JP4087144B2
Cited By
Two-wheeled vehicle
US12434520B2